Relationship of regional and whole-body morphology to vertical jump in elite soccer players: a data-driven approach - Bongiovanni, T.; Rossi, A.; IAIA, F. M.; Di Baldassarre, A.; Pasta, G.; Manetti, P.; Alberti, G.; Trecroci, A. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: This study aimed to analyze the relationship of regional and whole body morphology to vertical jump performance and to compare the morphological features outlining high and low performers in professional soccer players. METHODS: Twenty-one male soccer players were recruited. Whole and regional (upper and lower limbs) features were obtained in the form of body dimensional measurements. Then, all players were tested for vertical jump performance. A data-driven approach was used to group players according to their jump performance parameters (high vs. low). RESULTS: The regional morphological features presented higher correlations with vertical jump than whole body features. High and low performers were significantly different among upper- and lower-limb morphology. No differences were observed among whole body features. CONCLUSIONS: These findings indicate that, rather than the whole body, the use of morphological features linked to specific body regions may ensure a better interpretation of the soccer players` physical potential in jump performance.